From Scroll to Stroll: How Ibarbo Park Uses TikTok to Drive Tourist Engagement - Irfani, Susmita; Haq, Mochammad Fauzul (Jurnal Paradigma, 2025)
The rapid development of social media has made platforms like TikTok a strategic medium for promoting tourism destinations, especially among younger audiences. Ibarbo Park, a developing recreational site in Yogyakarta, utilizes TikTok to build awareness and attract visitors through engaging and interactive content. This study aims to explore the content management strategy implemented on TikTok by Ibarbo Park in promoting its tourism destination. The study aims to get deep understanding how digital content can influence public interest and drive engagement in the tourism sector. Employing a qualitative descriptive method, data were collected through in-depth interviews with content managers and visitors, observations of TikTok activities, and documentation. The research adopts the Circular Model of SOME to analyze the stages of content planning, interaction, and evaluation, while also using the 5A framework to understand audience behavior, from awareness to advocacy.